Gender and age structure of small mammals of anthropogenic regions of Northern Kazakhstan - Zakanova, A.N.; Yerzhanov, N.T.; Litvinov, Yu.N. (Fundamental and Experimental Biology, 2023)
The research was conducted in the spring-summer period of 2021 on the territory of northern Kazakhstan, where the Pavlodar region is located. The features in the sexual and age structure of populations were consid-ered. Populations live in the vicinity of two large heavy industry enterprises and a control area. The sources of anthropogenic impact were the Pavlodar Aluminum Plant and the Kazakhstan Electrolysis Plant. Research objective: to determine the dependence of the sex and age structure of small mammals on the proximity to the source of anthropogenic pollution of the area. The study area was divided into impact, buffer, background and control. Conclusions were drawn about the permanent effect of pollutants on the micromammalia organisms. There is a violation in the ratio of the number of females and males in the populations as they approach the sources of pollution. There is an increase in reproduction of individuals. The fertility of females of technogenic territories is higher than the control ones. The percentage of fingerlings, adults and overwintered animals differs. The impact territories have the largest number of young organisms and the smallest number of overwintered micromammalia. In the control area, there is a predominance of adults and pre-hibernating individuals. The age group of animals was determined by weight, body size, relative qualities (condition of the coat). There was no up-to-date information on the impact of anthropogenic impact on the gender and age structure of communities and populations of northern Kazakhstan. The results of this research will be useful in the process of planning a residential area of the region.